Mathematical argumentation in middle school - the what, why, and how : a step-by-step guide with activities, games, and lesson planning tools /: a step-by-step guide with activities, games, and lesson planning tools. (2017) - (Mathematics teacher), Knudsen, Jennifer; Stevens, Harriette; Lara-Meloy, Teresa; Kim, Hee-Joon; Schechtman, Nikki
No abstract available